Analisis Komoditi Ekonomi Non Migas yang Potensial Sebagai Pengembangan Sektor Unggulan di Desa Kalangan: SWOT Analisis - Nugraha, Rizki Bayu; Saputra, Ardian Gilang; Khusnayan, Belayunisa Risqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Law Number 6 of 2014 concerning village regulation is designed to support the development of village potential and assets in order to improve shared prosperity and encourage economic growth in village communities. This provides an opportunity for each village to optimize all its potential. It is important to note that Kalangan Village, located in Klego District, Boyolali Regency, faces challenges in maximizing its natural potential. In this context, this research aims to identify and map the potential of Kalangan Village, using a qualitative approach strengthened by SWOT, IFE and EFE analysis. Several problems found from the results of this research include: 1) lack of product innovation; 2) Lack of access to technology and resources to manage waste efficiently; 3) lack of citizen creativity in marketing; 4) Lack of community outreach and training regarding technological advances; 5) Lack of knowledge about environmentally friendly ways to manage sawdust waste. The results of field observations show that Kalangan Village is very suitable for developing a charcoal briquette product business as a solution to utilize existing potential. With this approach, Kalangan Village can minimize the problems found. Strategic recommendations involve entrepreneurship training, collaboration between stakeholders, and government support. By implementing this solution, it is hoped that Kalangan Village can optimize non-oil and gas economic potential, improve community welfare, and achieve environmental sustainability.